PENERAPAN TENUN GRINGSING PADA ELEMEN DEKORATIF DEVALI RESTAURANT HOTEL FOUR POINTS SEMINYAK BALI - Rabbani, Nabila Rifqi; Saryanto, Saryanto (ATRAT: Jurnal Seni Rupa, 2025)
As tourism develops in the Bali area, it is directly proportional to the increase in city hotels which provide various facilities. Four Points Hotel in Seminyak Bali is a city hotel with a four star classification that provides facilities for guests on holiday and business trips by paying attention to the main function of the hotel and enhancing aesthetics to be applied to every interior element. Aesthetics of Processing (motifs) of Gringsing Woven Fabric as a Decorative Element in De Vali Restaurant Interior Design Planning is research that discusses the transformation and implementation of gringsing woven fabric motifs in various decorative elements of De Vali Restaurant interior planning, through consideration of motifs, functions and symbolic meanings. The transformation of the shape of the motif is carried out through an aesthetic approach in accordance with the principles of design aesthetics, with an emphasis on three elements, namely composition, proportion and color in the material. That is the planning for the interior renewal of the Four Points Hotel Seminyak Bali Restaurant so that it can become an attraction through a contemporary concept.